Catalogue of the Mesostigmata mites in Finland - Huhta, Veikko (Memoranda Societatis pro Fauna et Flora Fennica, 2016)
This catalogue of Mesostigmata found in Finland is based on published records, material deposited in the Zoological Museum of Turku University, and collections by the author, deposited in the Zoological Museum of Helsinki University. The total number of recorded species is 451, including 15 unidentified or undescribed species. 121 of the identified species were not previously reported from Finland. General distribution in Finland and preferred habitats of the species are given, or of rare species the details of the records.